PdII-Porphyrin Complexes – the First Use as Safer and Efficient Catalysts for Miyaura Borylation - Rao, Kanusu Umamaheswara; Venkateswarlu, Katta (Synlett, 2018)
We have developed a simple and convenient procedure for the preparation of pinacol arylboronates from aryl/heteroaryl bromides and bis(pinacolato)diborane using a PdII-porphyrin complex as a catalyst. Seven different PdII-porphyrin complexes (PdII-TmHPP, PdII-TmCPP, PdII-TPP, PdII-TSTpSPP, PdII-TpCPP, PdII-TpTP, and PdII-TpAP) have been synthesized and investigated for their catalytic influence in the Miyaura borylation.
Keywords: Miyaura borylation; PdII-porphyrin complex; pinacol arylboronates